The Implementation of the Principle of Justice in Post-nuptial Agreement towards Mixed Marriage: Hope or Challenge? - Umar Haris Sanjaya (Universitas Ahmad Dahlan, 2021)
Introduction to the Problem: this research focuses on the actors of mixed marriage in Indonesia who have hope at the practice level. The hope arises from the Constitutional Court decision No. 69/VII/PUU/2015, which allows the formation of an asset separation agreement after the marriage takes place (post-nuptial agreement). The decision is followed up by two Circular Letters of relevant ministries: one is from the Ministry of Home Affairs No. 472.2/5876/Dukcapil, which guarantees that post-nuptial agreement is allowed in the Civil Registry (Dukcapil); as well as the one from Directorate Generals of Community Guidance under the Ministry of Religion No. B.2674/DJ/III/KW.00/9/2017. By enacting these instruments, Indonesia facilitates a hope to the mixed marriage, which is the hope of the ownership of the assets.Objectives of the Study: To identify the implication of the Constitutional Court decision No. 69/VII/PUU/2015 in practice, in lieu with the implication of the Circular Letters of the Ministry of Home Affairs No. 472.2/5876/Dukcapil and Directorate Generals of Community Guidance under the Ministry of Religion No. B.2674/DJ/III/KW.00/9/2017; also, to review the possibilities of those decisions and Circular Letters in the perspective of Indonesian family law, would it be a hope or a challenge?Methodology: This is normative-juridical research, which implements a doctrinal approach to analyze the problems.Findings: Post-nuptial agreement is allowed and having legal implications to the parties to the marriage bond. Ministry of Home Affairs and the Ministry of Religion have facilitated the Constitutional Court decision by enacting their respective Circular Letters to guide the civil registry officials in responding to the post-nuptial agreement.Paper Type: Research Article